Face-to-face and Cyber Victimization among Adolescents in Six Countries: The Interaction between Attributions and Coping Strategies - Wright, Michelle F.; Yanagida, Takuya; Machackova, Hana; Dedkova, Lenka; Sevcikova, Anna; Aoyama, Ikuko; Shu, Chang (Springer Heidelberg, 2018)
The purpose of this study was to examine the impact of publicity (private, public) and medium (face-to-face, cyber) on the associations between attributions (i.e., self-blame, aggressor-blame) and coping strategies (i.e., social support, retaliation, ignoring, helplessness) for hypothetical victimization scenarios among 3,442 adolescents (age range 11-15 years; 49% girls) from China, Cyprus, the Czech Republic, India, Japan, and the United States. When Indian and Czech adolescents made more of the aggressor-blame attribution, they used retaliation more for public face-to-face victimization when compared to private face-to-face victimization and public and private cyber victimization. In addition, helplessness was used more for public face-to-face victimization when Chinese adolescents utilized more of the aggressor-blame attribution and the self-blame attribution. Similar patterns were found for Cypriot adolescents, the self-blame attribution, and ignoring. The results have implications for the development of prevention and intervention programs that take into account the various contexts of peer victimization.
Keywords: Cyber victimization; Cyberbullying; Victimization; Coping; Attribution; Culture